2014
DOI: 10.1371/journal.pone.0100724
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of the Incidence and Prevalence of Stroke in Africa: A Systematic Review and Meta-Analysis

Abstract: BackgroundStroke is increasingly becoming a challenging public health issue in Africa, and the non-availability of data has limited research output and consequently the response to this burden. This study aimed to estimate the incidence and prevalence of stroke in Africa in 2009 towards improved policy response and management of the disease in the region.MethodsA systematic search of Medline, EMBASE and Global Health for original population-based or hospital-based studies on stroke was conducted. A random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
150
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(163 citation statements)
references
References 40 publications
10
150
2
1
Order By: Relevance
“…The higher proportion of stroke in upper-middle-income countries and urban settings compared to low-income countries and rural environments as shown in the present study and in previous reviews [6,8,43] are in line with convergence of increasing income level, urbanisation and cardio-vascular disease predictors.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The higher proportion of stroke in upper-middle-income countries and urban settings compared to low-income countries and rural environments as shown in the present study and in previous reviews [6,8,43] are in line with convergence of increasing income level, urbanisation and cardio-vascular disease predictors.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reviews had little representation of LMICs [44], others were based on regional [6,8,[45][46][47][48], country [28,49,50] or population-specific analysis [28,49,50]. There are also global reviews of stroke with few studies in LMICs [1,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the current epidemiological transition driven by rapid economic development and combined effects of population growth and aging, and sociocultural changes, there is huge concern of continuous increase in the prevalence of stroke in LMICs including Nigeria, and among relatively younger populations [2]. Recent systematic review of population-based studies revealed a consistent evidence that the prevalence of stroke and its major risk factors particularly high blood pressure were now higher in LMICs compared to high income countries and that young adults who present with stroke were unaware of their high blood pressure [2], [5], [6] and [7]. These important revelations were poorly known or underexplored in the rural areas of most LMICs such as in the Niger Delta region in Nigeria.…”
Section: Introductionmentioning
confidence: 99%